2014
DOI: 10.1186/1748-717x-9-43
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of tomotherapy treatment planning for patients with bilateral hip prostheses

Abstract: BackgroundTo determine the effect of different imaging options and the most efficient imaging strategy for treatment planning of patients with hip prostheses.MethodsThe planning kilovoltage CT (kVCT) and daily megavoltage CT (MVCT) studies for three prostate cancer patients with bilateral hip prostheses were used for creating hybrid kVCT/MVCT image sets. Treatment plans were created for kVCT images alone, hybrid kVCT/MVCT images, and MVCT images alone using the same dose prescription and planning parameters. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…A limitation of this study is that other approaches to improving calculation accuracy for patients with metal implants, namely the use of other calculation methods (e.g., Monte Carlo 34 and Grid-Based Boltzmann Solvers 35 ) and MV imaging, 36 were not investigated. Another limitation is that in our evaluation of various commercial artifact reduction algorithms we chose clinical cases in which treatment beams traverse metal implants.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of this study is that other approaches to improving calculation accuracy for patients with metal implants, namely the use of other calculation methods (e.g., Monte Carlo 34 and Grid-Based Boltzmann Solvers 35 ) and MV imaging, 36 were not investigated. Another limitation is that in our evaluation of various commercial artifact reduction algorithms we chose clinical cases in which treatment beams traverse metal implants.…”
Section: Discussionmentioning
confidence: 99%
“…Although challenging, IMRT planning is feasible in a patient with bilateral hip prostheses, 127 and class solutions have been proposed 128, 129. Megavoltage CT imaging, if available, may provide better imaging of pelvic anatomy and may be useful as a tool for electron density calibration during EBRT planning 130, 131. There is some limited evidence that MRI scanning may also be helpful for target delineation for patients with bilateral hip prostheses 132, 133.…”
Section: Techniques Of Patient Immobilization and Setupmentioning
confidence: 99%
“… 128 , 129 Megavoltage CT imaging, if available, may provide better imaging of pelvic anatomy and may be useful as a tool for electron density calibration during EBRT planning. 130 , 131 There is some limited evidence that MRI scanning may also be helpful for target delineation for patients with bilateral hip prostheses. 132 , 133 EBRT planning requires careful collaboration among radiation oncologists, physicists, and dosimetrists and should include recognition of the uncertainty in target volume definition and dose calculations.…”
Section: Techniques Of Patient Immobilization and Setupmentioning
confidence: 99%
“…Other authors have shown that CT scans acquired with MV-range energy spectra can provide a more accurate representation of the effect on megavoltage treatment beam interactions with dense objects. 14,15 This is not a practical alternative in most clinics, hence the need for a material assignment methodology based on commonly available kV-range CT datasets.…”
Section: Discussionmentioning
confidence: 99%